PRACTICAL STATISTICAL PACKAGE FOR SOCIAL SCIENCES (SPSS) TRAINING AND RESEARCH COMPETENCE AMONG STUDENTS AT THE UNIVERSITY OF NAIROBI (LOWER KABETE CAMPUS) - Kimani, John Githii (Journal of Statistics and Actuarial Research, 2018)
Purpose: The purpose of the paper is to assess the effectiveness of the practical SPSS training on students' research competency among undergraduate and postgraduate students at the University of Nairobi, Lower Kabete Campus. Methodology: A causal research design was used to establish the relationship between practical SPSS training and research competence of students. The target population was 160 students and a census was adopted. A questionnaire was administered at the end of the training to capture the pre and post training experience and test the effectiveness of the training. The analysis of the data was conducted through descriptive and inferential statistics. In particular, frequencies, means, standard deviations and paired t-test were used. Results: The post training evaluation results reveal that majority of the respondents had low knowledge in data entry, descriptive statistics, regression and correlation analysis, parametric and non-parametric analysis, and journal article extraction and publication. Results also reveal that the level of knowledge significantly increased after the training. This is supported by the paired t-tests conducted on each aspect of training. Unique Contribution to Theory, Policy and Practice: It was recommended to the campus management that frequent trainings should be organized at the convenience of the campus. It was suggested that university should consider supporting the training financially or the students to be requested to pay a token fee to make the training sustainable. Other financing approaches to enhance sustainability included having the consultant seeking funding from the National Research Fund. It was suggested that the training be made compulsory for all students undertaking Business Research Methods and points to accrue once they attend the training. The results were useful in theory building as they validated the efficacy of practical training pedagogical approaches.